The main aspects of medical supply in armed forces of NATO member countries - M. V. Bilous; O. P. Shmatenko; O. A. Ryzhov; D. V. Drozdov (Zaporozhye State Medical University, 2016)
Introduction. Nowadays medical supply system of Ukrainian military men does not fully correspond to the current needs of the troops, and has to be improved. Further direction of Ukrainian Armed Forces development demands functioning medical service on the ground of logistics management concept. Aim. In order to form the unified methodological approach to the optimization of logistics management of pharmaceutical provision of Ukrainian Armed Forces, a review of foreign and domestic scientific sources and the existing legal framework on this issue will be done. Materials and Methods. On this issue the review of foreign and domestic scientific sources and the existing legal framework has done to reach the aim of our work. Investigation methods were bibliographic and analytical ones. Results. In these review the peculiarities of military medical services of the armed forces of several NATO member countries have been studied, the main aspects of medical supply in the armed forces of NATO countries have been considered. The results of these studies indicate the need of advanced research, using the method of system analysis, structural organization and conceptual principles of logistics management of pharmaceutical provision in the armed forces of the Alliance countries. In the future, it is necessary to choose the system of logistics management of medical supply which is the most efficient and the closest in structure to the Ukrainian system and apply the best international practices of optimization flow of processes. The integration of the two models - Ukrainian and European ones helps to minimize the cost of reforming the system of logistics and standardization of Ukrainian Armed Forces. Conclusion. It was revealed that each of country - NATO member has its own system of organization of medical supply of troops, but existing NATO standards of medical support and common terminology databases allow all Alliance members, if necessary, work together. The need of development of a conceptual model of optimization of management of flow processes in the medical supply of Ukrainian Armed Forces in accordance with NATO standards has been found. Also the necessity of regulatory fixation of developed model in the domestic legislative framework and practice of military health care of Ukraine exists. It provides the opportunities and new trends of development of medical support logistic systems directed on the strengthening of Ukrainian Armed Forces fighting efficiency.